Optimization of the cry1Ah1 Sequence Enhances the Hyper-Resistance of Transgenic Poplars to Hyphantria cunea - Xu, Chen; Wei, Hui; Wang, Like; Yin, Tongming; Zhuge, Qiang (Frontiers in Plant Science, 2019)
Abstract Increased expression of the insect control protein genes of B. thuringiensis in Populus has been critical to the development of genetically improved plants with agronomically acceptable levels of insect resistance. Bacillus thuringiensis (Cry1Ah1) proteins with highly specific toxicity against Hyphantria cunea were screened using an indoor bioactivity assay to obtain hyper-resistant transgenic poplars. Then, the Cry1Ah1 sequence was optimized and transformed according to the optimal codon in poplar using software of our own design (http://120.79.60.226:8080/u/chen/w/codonpoplar). A vector was constructed to transform poplar NL895. The Cry1Ah1 gene was transformed to poplar NL895 and six transgenic lines were obtained. The expression and insecticidal effect of the Cry1Ah1 gene in transgenic poplar were evaluated by PCR and ELISA, and the specific indoor activity and field insecticidal activity against H. cunea were compared with a control. We concluded that the insecticidal activity of the transgenic NL895 was significantly better against lower instar larvae of H. cunea than against higher instar larvae. The mortality and pupation rates clearly differed among the various instar larvae and between transgenic and non-transgenic poplar. We obtained poplar seedlings with hyper-resistance to H. cunea by screening Bt genes and optimizing their genetic sequence.